Beliefs about medicines among Hong Kong hospital outpatients. (16th March 2017) - Wan, Bosco K.F.; Cheung, Walter H.K.; Ball, Patrick A.; Jackson, David M.; Maynard, Gregg J.
Abstract: Objectives: (1) To identify demographic characteristics associated with different patients' belief attitudes among older Hong Kong hospital outpatients. (2) To identify important implementation criteria for developing a more effective adherence‐improving intervention. Methods: Six hundred and ninety‐eight patients completed a questionnaire consisting of demographic information and Belief about Medicines Questionnaire. Findings were statistically analysed. Key findings: Among respondents, 56.9% were either in the hesitant (Mixed‐feelings and Indifferent) or negative (Distrustful) medication belief constructs. The majority of these patients were younger females, with better education, taking fewer regular medications and for shorter duration. Rheumatoid and gout accounted for 46.1% of cases in the Distrustful construct, while cardiovascular and diabetic conditions accounted for 63.8% of cases in the positive (In‐favour) construct. Patients' concerns about medications were reaffirmed to be a predominant factor affecting medication beliefs. The mean Necessity–Concern Differential scores in the two hesitant constructs illustrated that patients within these two constructs were more pliant towards medicines and, therefore, were predicted to be more subject to modification. Conclusions: Our results identified the demographic characteristics of patients with negative or hesitant belief attitudes about medicines. In order to effectively achieve improvement in long‐term beliefs about medications, the design of interventions should target positively modifying belief attitudes in these two patient groups. Furthermore, addressing patients' concern about their medicines was reaffirmed to be an important criterion for researchers to focus on when designing effective interventions in the future.